Solving the bin location-allocation problem for household and recycle waste generated in the commune of Renca in Santiago, Chile - Letelier, Carina (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
In the commune of Renca in Santiago, Chile, the household waste is currently collected on the kerbside and then thrown in the rear of a compactor truck. This system becomes inefficient when not all citizens are always serviced, yielding high overall collection costs and negative impacts on the environment and the society. Recently, recyclable waste collection sites have been situated throughout the commune, which need to be examined with respect to population coverage and average travel distances to these sites. This study employs mixed-integer linear programming models and geographic information systems to solve the bin location-allocation problem for household and recyclable waste separately. The results are shown for different values of waste generation, bin capacities, and travel distances, in addition to considering the users' and municipality's preferences in the decision-making process. The proposed recyclable waste bin locations present a more efficient solution than the existing collection sites in the commune of Renca since more users are serviced within a shorter travel distance to dispose of their recyclable waste